PREDICTION OF PRE-ECLAMPSIA AND FETAL GROWTH RESTRICTION BY UTERINE ARTERY DOPPLER: A SYSTEMATIC REVIEW (The Research of Medical Science Review, 2025)
Background: Pre-eclampsia and fetal growth restriction (FGR) are major causes of maternal and perinatal morbidity and mortality. Early detection of at-risk pregnancies is crucial for timely intervention. Uterine artery Doppler ultrasonography is a noninvasive technique used to assess uteroplacental circulation, which may help predict these complications.Methods: A comprehensive literature search was conducted using databases including PubMed, Google Scholar, Scopus, CINAHL, and LILACS. From 4121 initially identified records, 10 studies met the inclusion criteria after screening and duplicate removal. These studies assessed the role of uterine artery Doppler ultrasound in predicting placental insufficiency-related complications.Results: Most studies demonstrated that abnormal uterine artery Doppler findings in the second trimester, such as elevated PI or the presence of bilateral diastolic notching, were significantly associated with the development of pre-eclampsia and FGR. The predictive value was higher when combined with maternal risk factors or biochemical markers.Conclusion: Uterine artery Doppler is a valuable screening tool for predicting pre-eclampsia and fetal growth restriction, especially when used in the second trimester. It may help in stratifying risk and guiding closer monitoring and early intervention in high-risk pregnanciesive.